Avaliação dos conhecimentos e conteúdos curriculares sobre sexo e sexualidade de adolescentes nas escolas públicas de Pitangui - MG - Alberto Elias Lopes Cancado (2007)
Introduce: This descriptive cross-section study, developed in 2006, was aimed at evaluating the understanding of sex and sexuality among 10 to 15 year-old students of five public schools in the city of Pitangui, Minas Gerais State. Methods: The methodology included a 23-questions questionnaire based on the Ministry of Education Curricular Parameters - MEC (PCNs), the curriculum proposed by the Minas Gerais State Secretary of Education and on the textbooks adopted in the public schools. Four questions assessed the source of the students knowledge of sex and sexuality: Who? Where? How many times per year? Which subjects were most discussed in school? The data collected included name of school, student age (years and months), school level, gender and indication of either day or evening classes. All questions included the option I dont know, in case the respondent hadno knowledge of the subject. Measures were taken not to allow the students to interact with their peers while answering the questions, give them sufficient time to complete their answers, have qualified teachers applying the questionnaire and have the researcher checking of the questionnaires delivered or returned due to absence of some subjects. Results: From a valid total of 1421 (86.5%) teenagers interviewed,only 524 (32.9%) effectively participated in the survey. 863 students (52.5%) refused to provide answers and 34 (2.1%) were absent. 58.2% were female and 41.8% male. 39.6% of the valid answers contained errors, 43.3% of the interviewees provided correct answers but 17.1% were unable to answer for lack of knowledge. The highest percentage of correct answers was supplied by the oldest female teenagers in theadvanced grades. 79.1% of the respondents were not able to provide a correct answer about the exact location of fertilization in the reproductive system. 83.3% of the subjects provided the correct name of the male reproductive cell, but 16.7% were not able to identify where the production of spermatozoids occurs. In the field of physiology, the question about the first female transformation during puberty received 63.7% of correct answers. 38% of the teenagers provided wrong answers for thequestions on the relation between pregnancy and menstruation and 60.8% said they did not know what menarche meant. The definition of responsible sexuality was correctly provided by 73.8% of the interviewees while the concept of sexual relation was mistakenly defined by 71.7%. 23.1% of the students could not define masturbation. Mothers and television were considered the two main sources of knowledge about sex and sexuality. The school offers an average of two lectures per year on the subject of sex and sexuality focusing mainly on the description of thereproductive system. Conclusion: The feminine gender provided the highest percentage of respondents. The highest percentage of correct answers for the questions about anatomy, physiology and sexuality was obtained in the advanced levels (7th and 8th grades), the masculine gender showing the highest percentage of errors and lack of knowledge. A final conclusion was that 5th to 8th grade students enrolled in the public schools of Pitangui, Minas Gerais State, have a poorunderstanding of sex and sexuality. To some extent, the high level of unwillingness to provide data tended to support the statistical results.